Gas Tamponade Improved Cilio-Choroidal Effusion Induced by an Ab Interno Trabeculotomy with a Microhook: Two Cases - Otsuka M; Tojo N; Yanagisawa S; Hayashi A (International Medical Case Reports Journal, 2024)
Mitsuya Otsuka, Naoki Tojo, Shuichiro Yanagisawa, Atsushi Hayashi Department of Ophthalmology, Graduate School of Medicine and Pharmaceutical Sciences, University of Toyama, Toyama, JapanCorrespondence: Atsushi Hayashi, Department of Ophthalmology, Graduate School of Medicine and Pharmaceutical Sciences, University of Toyama, 2630 Sugitani, Toyama, 930-0194, Japan, Tel +81-76-434-7363, Fax +81-76-434-5037, Email ahayashi@med.u-toyama.ac.jpPurpose: We treated two patients with ciliary detachment due to an ab interno trabeculotomy. The ciliary detachment was improved by the use of sulfur hexafluoride (SF6) gas or octafluoro propane (C3F8) tamponade.Patients and Methods: Patient 1 was a 52-year-old Brazilian man with primary open angle glaucoma (POAG). His preoperative intraocular pressure (IOP) was 29 mmHg. Patient 2 was a 57-year-old Japanese woman with POAG. Her preoperative IOP was 35 mmHg. Both patients underwent an ab interno trabeculotomy with a microhook. They caused ciliary detachment as a postoperative complication. We could observe their ciliary detachment with anterior segment optical coherence tomography (AS-OCT). Hypotony persisted for 2 months and the patients’ ciliary detachment had not improved. They each underwent a pars plana vitrectomy (PPV) with simultaneous 20% SF6 filling.Results: In Patient 1, the use of the SF6 gas tamponade successfully attached the ciliary body. His IOP was increased to 30 mmHg after this resolution of the ciliary detachment. He underwent additional tube shunt surgery. For Patient 2, the SF6 gas tamponade improved the ciliary detachment but the ciliary body could not be attached. We injected 0.6 cc of 100% C3F8 gas into the vitreous cavity, and this gas tamponade was able to attach the ciliary body.Conclusion: AS-OCT is very useful to evaluate ciliary detachment. PPV+Gas tamponade can be a treatment option for ciliary detachment.Keywords: ab interno trabeculotomy, ciliary detachment, cyclodialysis, tamponade, microhook